A study on linkages of economic variables toward Kuala Lumpur composite index / Wan Mohammad Firdaus Wan Bidin - Wan Bidin, Wan Mohammad Firdaus (2011)
Now a days, number of investors increase in stock investment. Prediction, rumors and economy stability influent action of the investor to start invest. Economy variables changes in this sector will cause momentum of the changes the performance stock price. The data collected by annually and Multiple Linear Regression Analysis used to estimate the functions related between independent variable (Base Lending Rate (BLR) and Gross Domestic Product (GDP), Foreign Direct Investment (FDI) and Consumer Price Index (CPI)) and dependent variable (performance Kuala Lumpur Composite Index). Based on the findings and result of analysis, the researcher can conclude that the KLCI has a significant relationship between Base Lending Rate (BLR) and Gross Domestic Product (GDP), and Consumer Price Index while, Foreign Direct Investment(FDI) do not has a significant relationship between Kuala Lumpur Composite Index during testing in test of significant even though 3 variable shows the positive relationships towards KLCI except Consumer Price Index (CPI). This study has achieved researcher objective where from the outcome, the researcher can see linkages of economic variables toward KLCI